Work-Family Conflict Impact on Psychological Safety and Psychological Well-Being: A Job Performance Model - Obrenovic, Bojan; Jianguo, Du; Khudaykulov, Akmal; Khan, Muhammad Aamir Shafique (Frontiers in Psychology, 2020)
In a modern working environment characterized by new technology and work assignments extended to personal time, employees are expected to balance multiple roles while maintaining maximum productivity. Past studies analyzed work-family conflict and its connection to job performance, without adequate integration of psychological factors into the research model. This study aims to fill the gap and explain the impact of work-family conflict and psychological factors on job performance. To explore the association between work-family conflict and job performance and measure the effects on psychological safety and psychological well-being, an empirical study was conducted on a sample of 277 company employees in Bahrain. The online questionnaire used five-point Likert-scales adopted from previous studies to measure the variables of the research model. In the structural model, relationships between work-family conflict, psychological well-being, psychological safety, and job performance were tested. Confirmatory Factor Analysis with Maximum likelihood estimation was performed by using SEM software AMOS version 23. The findings of the study suggest there is a negative impact of work-family conflict on psychological safety and psychological well-being. This study is significant since it detaches from the prior researches focused on observing the repercussions of work-family conflict in workers’ well-being, and centers on the analysis of job performance instead. The findings show that psychological well-being and psychological safety influence job performance. When the psychological well-being and psychological safety of employees are unsatisfactory, the job performance will decrease accordingly. The mediation test indicated that work-family conflict had an indirect influence on job performance when psychological safety and psychological well-being were mediators. The study contributes to a better understanding of work-family conflict, psychology of employees, and job performance. The study provides valuable insight to organizations on ways to increase employees’ effectiveness and ensure better performance by preventing work-family conflict from occurring.